Pemberdayaan Berbasis Syariah untuk Perempuan di Pedesaan Melalui Model Pemberdayaan Grassroots Microfinance Shariah - Sabirin Sabirin (PSGA LP2M IAIN Pontianak, 2016)
Women have an important role in national development. One way to make room for women in the national development process is by provide a space for them to be more empowered. With the empowerment of women, especially women in the countryside, hopefully they can be more productive, have the courage to take risks in business,self-sustainability, because women will tend to be more independent if they have income and economic activity. Women as part of society should be able to help themselves in different ways, especially with regard to their survival.This paper discusses the model of Grassroots Islamic Microfinance which is a model of Islamic-based financing institution forpoor families but productive especially for women in the countryside who does nothave an opportunity to obtain financing support from commercial microfinance such as banks. This model is an effort to encourage, provide access for women on countryside especially on capitalization, so that they can be more productive and independent in an effort to prosper themselves, their families and the general public.